At Westonci.ca, we provide clear, reliable answers to all your questions. Join our vibrant community and get the solutions you need. Join our Q&A platform to connect with experts dedicated to providing accurate answers to your questions in various fields. Explore comprehensive solutions to your questions from knowledgeable professionals across various fields on our platform.

system of equations,

3x - 6y =2

5x + 4y = 1


Sagot :

logo88
3x-6y=2 (label equation 1)
5x+4y=1 (label equation 2)
-6y=-3x+2 (rearranged equation 1)
y=1/2x-1/3 (label equation 3)
 substitute equation 3 into equation 2 
5x+4(1/2x-1/3)=1
5x+2x-4/3=1
15x+6x-4=3 (multiplied everything by 3)

21x-4=3
     +4  +4
21x=7
x= 7/21
x=1/3

sub x=7/21 into equation 3
y= 1/2(1/3) -1/3
y= -1/6


Therefore x=1/3 and y= -1/6